2020
DOI: 10.3390/agriculture10010022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weather Conditions and Farming Systems on Size Distribution of Starch Granules and Flour Yield of Winter Wheat

Abstract: The size distribution of wheat-grain starch granules has an impact on the yield of fine flour. The aim of the study was to compare the impact of conventional (mineral fertilizers, pesticides) and organic farming treatments (cover crops, composted cattle manure) on (i) the size distribution of starch granules, (ii) the level of the first break whole and fine flour yield. The grain samples of winter wheat cv Fredis were taken from a long-term field crop rotation experiment established in 2008 at the Estonian Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The quality of the dough was assessed through its rheological properties and the results showed that quality depended on a combination of several factors, but in particular on the quantity and quality of protein and gluten, which in turn depended on both of the studied trial factors (weather conditions in trial years and N treatment, i.e., mineral or organic N availability during grain filling period). The protein and gluten content and therefore, the wheat-dough quality, were better in 2014 and 2016, when the grain yield level was lower [20], which is also in line with the findings of Giancaspro et al [31]. The mean protein and gluten content over the trial years were highest in flours obtained from N treatment N150.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The quality of the dough was assessed through its rheological properties and the results showed that quality depended on a combination of several factors, but in particular on the quantity and quality of protein and gluten, which in turn depended on both of the studied trial factors (weather conditions in trial years and N treatment, i.e., mineral or organic N availability during grain filling period). The protein and gluten content and therefore, the wheat-dough quality, were better in 2014 and 2016, when the grain yield level was lower [20], which is also in line with the findings of Giancaspro et al [31]. The mean protein and gluten content over the trial years were highest in flours obtained from N treatment N150.…”
Section: Discussionsupporting
confidence: 89%
“…As organic production becomes more widespread [19], and farmers are urged to decrease mineral nitrogen input, it is important to clarify the extent to which organic fertilization affects gluten accumulation and starch-granule formation during grain filling, whilst the interaction of gluten and starch granules on the dough properties of cereals grown in organic or conventional systems invites further exploration. Earlier, we demonstrated that in addition to the fertilizing regime, local weather conditions significantly influence N availability and the protein content of grains [20].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The organic farming system has been adapted for many climate zones and local conditions [37]. Agronomic performance and quality traits are affected by environmental conditions and growing season [41][42][43][44]. However, nitrogen (N) fertilization management and the irregular availability of N due to factors influencing mineralization in the soil are two of the biggest challenges for organic farming [42,43].…”
Section: Protein Contentmentioning
confidence: 99%